Analisis Peran Kegiatan Literasi dalam Meningkatkan Minat Baca dan Keterampilan Literasi Siswa di SMP Negeri 6 Kota Serang - Aat Hartati; Ameliani Ameliani; Fitri Thania Ambari; Heni Setya Mawarni; Jumrotul ‘Aini; Rizki Sudrajat; Wiyola Wiyola (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to analyze the role of literacy activities in increasing students' interest in reading and literacy skills at SMP Negeri 6 Serang City, as well as formulating solutions to factors inhibiting literacy activities as a form of effort to develop activities to be more effective. The literacy activities in question include various reading, writing activities, as well as presenting the results of reading or work both outside teaching and learning activities (KBM) hours (every Thursday) and during teaching and learning activities (KBM). This research uses qualitative research methods with interview data collection techniques and literature studies. This research came up with results that show that literacy activities contribute a positive influence to reading interest and literacy skills, and can explore the interests and talents of students at SMPN 6 Serang City. This research also succeeded in revealing at least 4 factors that support the success of literacy activities in schools and 5 inhibiting factors along with solutions as an effort to overcome obstacles or challenges faced in making the goals of literacy activities a success.